Migration, location and provision of support to old-age parents: The case of Romania - Zachary Zimmer; Codrina Rada; Catalin Augustin Stoica (The University of Utah, Department of Economics, 2013)
The combined demographic developments of population aging and high rates of migration of young adults are consequential for older parents who face a potential decline in support from adult children. These developments also impact the lives of migrant adults who face the challenge of providing support to aging parents from a distance. Systematic data that allow examination of associations between the location of migrants and the provision of support to aging parents are difficult to find for Eastern Europe, a region undergoing enormous demographic and socio-economic transition. Using recently collected data from Romania, a country facing both rapid aging and out-migration, and building upon a family altruism framework, this study models provision of monetary and instrumental support as a function of migrant's location of residence, location of their siblings in relation to parents, and other characteristics that fall under domains of parental need, ability of migrant to provide, and predisposing characteristics of migrant and parent. Models are run using a mixed methods approach accounting for the random effects at the family level. Results indicate international migrants are more likely to give money while those migrating within Romania are more likely to provide instrumental support. Regardless of type of support or location of migrant, the probability of support increases when other sources are less available and when a parent has greater need. Results provide support for the altruistic framework and help to build upon the understanding of intergenerational exchanges within rapidly changing demographic environments.
Keywords: F22; F24; N30; R23; 330; population aging; migration; intergenerational support; Romania